The BFG - Dahl, Roald; Blake, Quentin (London : Puffin Books, 1984)
Kidsnatched from her orphanage by a BFG (Big Friendly Giant), who spends his life blowing happy dreams to children, Sophie concocts with him a plan to save the world from nine other man-gobbling cannybull giants.
4.9
3-6.
3-6
Keywords: Giants -- Juvenile fiction; Orphans -- Juvenile fiction; Giants -- Fiction; Orphans -- Fiction; Giants -- Fiction; Orphans -- Fiction